2016
DOI: 10.1074/jbc.m115.694562
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent Regulation of Erythropoietin Receptor Turnover and Signaling

Abstract: von Hippel-Lindau (VHL) disease is a rare familial cancer predisposition syndrome caused by a loss or mutation in a single gene, VHL, but it exhibits a wide phenotypic variability that can be categorized into distinct subtypes. The phenotypic variability has been largely argued to be attributable to the extent of deregulation of the ␣ subunit of hypoxia-inducible factor ␣, a well established target of VHL E3 ubiquitin ligase, ECV (Elongins/ Cul2/VHL). Here, we show that erythropoietin receptor (EPOR) is hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Based on these data, we suggest that the pathogenic assessment of mutations affecting this area should also include other putative pVHL hydroxylated-substrates beyond the sole HIF-1/2α, e.g. SPRY2 (37), ADRB2 (38), EPOR (39). Eleven interactors are found to be affected by surface C mutations.…”
Section: Protein Network Impaired By the Most Frequent Pvhl Mutationsmentioning
confidence: 89%
“…Based on these data, we suggest that the pathogenic assessment of mutations affecting this area should also include other putative pVHL hydroxylated-substrates beyond the sole HIF-1/2α, e.g. SPRY2 (37), ADRB2 (38), EPOR (39). Eleven interactors are found to be affected by surface C mutations.…”
Section: Protein Network Impaired By the Most Frequent Pvhl Mutationsmentioning
confidence: 89%
“…[103] showed for the first time that EPOR protein levels are regulated by PHD3/EglN3 -mediated prolyl hydroxylation on Pro419 and Pro426 residues (Fig. 6A).…”
Section: Novel Hydroxylation Targets and Their Cellular Functionsmentioning
confidence: 99%
“…Recently, another example of hydroxy-degron was described by Ohh and co-workers for the erythropoietin receptor (EPOR) [ 22 ]. EPOR is hydroxylated on Pro419 and Pro426 via PHD3, the resulting degrons have no sequence identity to LxxLAP motif, while localize within a proline-rich region ( figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the authors reported examples of pVHL mutants that retain proper binding and regulation of HIF-1 α while showing severe defect in binding EPOR. In particular, pVHL mutations classified as promoting VHL disease sub-phenotype 2C, showed a marked defect in binding to hydroxylated EPOR [ 22 ]. These findings suggest at least one novel molecular framework to explain the wide phenotypic variability in VHL disease.…”
Section: Introductionmentioning
confidence: 99%